Study on improving three-dimensional dynamic simulation model and equation of flexible fabric - Meiliang Wang; Mingjun Wang; Xiaobo Li (Advances in Mechanical Engineering, 2019)
The use of the traditional fabric simulation model evidently shows that it cannot accurately reflect the material properties of the real fabric. This is against the background that the simulation result is artificial or an imitation, which leads to a low simulation equation. In order to solve such problems from occurring, there is need for a novel model that is designed to enhance the essential properties required for a flexible fabric, the simulation effect of the fabric, and the efficiency of simulation equation solving. Therefore, the improvement study results will offer a meaningful and practical understanding within the field of garment automation design, three-dimensional animation, virtual fitting to mention but a few.